Zoological biobanks as a resource for microplastic analysis: a Py-GC-MS/MS case study on sea cucumbers - Valentin Dettling; Magali Albignac; Claire Laguionie; Jean-Baptiste Fini; Sarah Samadi; Alexandra ter Halle (Marine Pollution Bulletin, 2026)

Biodiversity impact of agricultural products in France: Greater differences across product types than food quality schemes - Sarah Huet; Abdoul Diallo; Julie Regolo; Ainhoa Ihasusta; Ludovic Arnaud; Valentin Bellassen (Ecological Economics, 2026)

Measurement of sawlog stacks on an individual log basis using LiDAR - Lukas Moik; Christoph Gollob; Tobias Ofner-Graff; Valentin Sarkleti; Tim Ritter; Andreas Tockner; Sarah Witzmann; Ralf Kraßnitzer; Karl Stampfer; Arne Nothdurft (Computers and Electronics in Agriculture, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Animal disease surveillance: How to represent textual data for classifying epidemiological information - Sarah Valentin; Rémy Decoupes; Renaud Lancelot; Mathieu Roche (Preventive Veterinary Medicine, 2023)

Genotoxicity and inflammatory potential of stainless steel welding fume particles: an in vitro study on standard vs Cr(VI)-reduced flux-cored wires and the role of released metals - Sarah McCarrick; Valentin Romanovski; Zheng Wei; Elin M. Westin; Kjell-Arne Persson; Klara Trydell; Richard Wagner; Inger Odnevall; Yolanda S. Hedberg; Hanna L. Karlsson (Archives of Toxicology, 2021)
Welders are daily exposed to various levels of welding fumes containing several metals. This exposure can lead to an increased risk for different health effects which serves as a driving force to develop new methods that generate less toxic fumes. The aim of this study was to explore the role of released metals for welding particle-induced toxicity and to test the hypothesis that a reduction of Cr(VI) in welding fumes results in less toxicity by comparing the welding fume particles of optimized Cr(VI)-reduced flux-cored wires (FCWs) to standard FCWs. The welding particles were thoroughly characterized, and toxicity (cell viability, DNA damage and inflammation) was assessed following exposure to welding particles as well as their released metal fraction using cultured human bronchial epithelial cells (HBEC-3kt, 5–100 µg/mL) and human monocyte-derived macrophages (THP-1, 10–50 µg/mL). The results showed that all Cr was released as Cr(VI) for welding particles generated using standard FCWs whereas only minor levels (

Adaptive divergence across Southern Ocean gradients in the pelagic diatom Fragilariopsis kerguelensis - Ute Postel; Barbara Glemser; Katherine Salazar Alekseyeva; Sarah Lena Eggers; Marco Groth; Gernot Glöckner; Uwe John; Thomas Mock; Kerstin Klemm; Klaus Valentin; Bánk Beszteri (Molecular Ecology, 2020)
The Southern Ocean is characterized by longitudinal water circulations crossed by strong latitudinal gradients. How this oceanographic background shapes planktonic populations is largely unknown, despite the significance of this region for global biogeochemical cycles. Here, we show, based on genomic, morphometric, ecophysiological and mating compatibility data, an example of ecotypic differentiation and speciation within an endemic pelagic inhabitant, the diatom Fragilariopsis kerguelensis . We discovered three genotypic variants, one present throughout the latitudinal transect sampled, the others restricted to the north and south, respectively. The latter two showed reciprocal monophyly across all three genomes and significant ecophysiological differences consistent with local adaptation, but produced viable offspring in laboratory crosses. The third group was also reproductively isolated from the latter two. We hypothesize that this pattern originated by an adaptive expansion accompanied by ecotypic divergence, followed by sympatric speciation.

Joint Multi-modal Parcellation of the Human Striatum: Functions and Clinical Relevance - Xiaojin Liu; Simon B. Eickhoff; Felix Hoffstaedter; Sarah Genon; Svenja Caspers; Kathrin Reetz; Imis Dogan; Claudia R. Eickhoff; Ji Chen; Julian Caspers; Niels Reuter; Christian Mathys; et al. (Neuroscience Bulletin, 2020)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)